A study with the aim to investigate the quality of Gronotoma micromorpha which attack the immature developmental stages of Liriomyza huidobrensis has been carried out. Such variables as body length measured from caput to the tip of abdomen, wing span and the length of tibia of hind leg were measured to represent parasitoid quality. The immature developmental stage period of the parasitoid was also recorded. The result indicated that a better quality Gronotoma was obtained when it was developed i - LA DAHA (HAYATI Journal of Biosciences, 2011)
A study with the aim to investigate the quality of Gronotoma micromorpha which attack the immature developmental stages of Liriomyza huidobrensis has been carried out. Such variables as body length measured from caput to the tip of abdomen, wing span and the length of tibia of hind leg were measured to represent parasitoid quality. The immature developmental stage period of the parasitoid was also recorded. The result indicated that a better quality Gronotoma was obtained when it was developed in the Liriomyza larvae fed on chinese cabbage with the average of 123.85 mm for body length, 253.45 mm for wing span, and 42.85 mm for the length of hind tibia, respectively. When Gronotoma was developed in the Liriomyza larvae fed on soy bean, its size became smaller with the average of 97.7 mm for body length, 214.3 mm for wing span, and 37.2 mm for the hind tibia. When it is developed in the Liriomyza on chinese cabbage host plant the immature developmental period of Gronotoma is sligthly shorter with the average of 18.4 and 17.3 days for which developed in the larvae and pupa respectively and on soy bean it become longer with the average of 19.2 days for in eggs, 19.9 days for that in the larvae. On chinese cabbage, Liriomyza tend to have bigger size for both flies and pupae.